Cooking and eating characteristics in upland and irrigated rice varieties - Farias, Francisco José Correia; la Cruz, Normita M. de (Pesquisa Agropecuaria Brasileira, 1995)
Twenty-eight Brazilian rice cultivars proceeding from the Germplasm Center of the International Rice Research Institute (IRRI), were tested as to the grain quality characteristics. Amylose contents gelatinization temperature and gel consistency were analyzed and discussed. The percentage of amylose content ranged from 15.0 to 27.0% by the simplified hand method and from 16.0 to 26.0% on the autoanalysis method. The alkali test values ranged from 2.0 to 7.0 for spreading. By the gel consistency method, the length ranged from 27.0 to 98.0 mm. The evaluated cultivars showed gel consistency which encompassed from hard, medium, mediumly soft and soft. The cultivars IAC 47, Lageado, EEA 201, Paga Dívida, EEPG 261, Vermelho Pernambuco, Dourado Agulha, IAC 416, Canela de Ferro and EEPG 269 were selected with excellent cooking and eating characteristics which will be able to serve as gene sources in the rice breeding program for grain quality.